Dampak Aplikasi Tiktok Pada Perkembangan Moral Anak Kelompok B Di Tk Muslimat Nu 13 Labuhan Kecamatan Brondong Kabupaten Lamongan - Siti Dewanti; Muslimin (Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
TikTok is a popular Application, easy to play, both adults and children, which greatly impacts their moral development. The focus of this research are: 1) Factors that influence group B students at Muslimat NU 13 Labuhan Kindergarten so that they are interested in the TikTok application? 2) What are the positive and negative impacts of the TikTok application on the moral development of group B children at the NU 13 Labuhan Muslimat Kindergarten? This study uses qualitative methods with descriptive analysis of interview data, observation, and documentation. Factors that influence children's interest in TikTok are: 1) Children often play TikTok 2) Facility support 3) Parents like to see children imitating the movements and songs on TikTok. The positive and negative impacts of the TikTok application on the moral development of group B children at Muslimat NU 13 Labuhan Kindergarten are 1) Generating self-confidence/courage in children 2) The emergence of creativity in children 3) Developing aspects of motor skills, language, creativity in children. The negative impacts are 1) The child's behavior is impolite 2) It is difficult to pay attention to lessons or simple commands 3) The child behaves arbitrarily 3) The child likes to sing and dance in inappropriate places 4) deviations from religious and moral values taught in Kindergarten Muslimat NU13 Labuhan.